From Genres to Modes. Premises for a Theory of Hybridity (ENTHYMEMA, 2023)
The article offers a contribution to the debate on hybridization, trying to overcome the schematisms concerning this concept. The premises for a theoretical discourse are identified in the aesthetics of conflict by Friedrich Nietzsche, who sees in the work of art the place of a struggle between opposing forces and thus lays the foundations for a distinction between sterile hybridizations and fruitful hybridizations. The reflections of the German philosopher allow the elaboration of a reflection on hybridization capable of renouncing the unilateral exaltation of mixtures as a phenomenon of modernity and of overcoming the theories that prefer genres in favor of those that prefer ways of being and styles of thought, which better allow us to describe the ontological status of semantic objects such as human beings and works of art. The analysis of Midnight’s Children will provide an example of this perspective.
Keywords: Hybridity; Identity; Conflictual aesthetics; Ways of being; Midnight's Children